2020
DOI: 10.1101/2020.06.11.20128306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance and health economic evaluation of the Mount Sinai COVID-19 serological assay identifies modification of thresholding as necessary to maximise specificity of the assay

Abstract: We evaluated the FDA approved SARS-CoV-2 immunoassay (developed at Mount Sinai, by Krammer and colleagues) for the identification of COVID-19 seroconversion and potential cross-reactivity of the assay in a United Kingdom (UK) National Health Service (NHS) hospital setting. In our "set up" cohort we found that the SARS-CoV-2 IgG was detectable in 100% of patients tested 14 days post positive COVID-19 nucleic acid test. Serum samples taken from pregnant women in 2018 were used as a negative control group with ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Rushworth et al conducted a performance evaluation of the Mount Sinai SARS-CoV-2 IgG antibody ELISA, and observed no false positive results in a cohort of negative control samples (n = 50) drawn from presumed healthy pregnant women pre-COVID-19. 32 In the present study, two reactive results were observed in prepandemic samples taken from pregnant women using the Elecsys Anti-SARS-CoV-2 immunoassay, which could be the result of an unknown cross-reactant.…”
Section: Discussionmentioning
confidence: 50%
“…Rushworth et al conducted a performance evaluation of the Mount Sinai SARS-CoV-2 IgG antibody ELISA, and observed no false positive results in a cohort of negative control samples (n = 50) drawn from presumed healthy pregnant women pre-COVID-19. 32 In the present study, two reactive results were observed in prepandemic samples taken from pregnant women using the Elecsys Anti-SARS-CoV-2 immunoassay, which could be the result of an unknown cross-reactant.…”
Section: Discussionmentioning
confidence: 50%
“…At present, there are limited data available on the performance of other commercially available serological assays for SARS-CoV-2 in pregnant women. Rushworth et al conducted a performance evaluation of the Mount Sinai SARS-CoV-2 IgG antibody ELISA and observed no false positive results in a cohort of negative control samples ( n = 50) drawn from presumed healthy pregnant women pre-COVID-19 [ 31 ]. In the present study, two reactive results were observed in pre-COVID-19 samples from pregnant women, which could be the result of an unknown cross-reactant.…”
Section: Discussionmentioning
confidence: 99%